A Scoping Review of Assessment Methods Following Undergraduate Clinical Placements in Anesthesia and Intensive Care Medicine - O'Connor, Enda; Doyle, Evin (Frontiers in Medicine, 2022)
Introduction Anaesthesia and intensive care medicine are relatively new undergraduate medical placements. Both present unique learning opportunities and educational challenges to trainers and medical students. In the context of ongoing advances in medical education assessment, our scoping review sought to describe current research around medical student assessment after anaesthesia and intensive care placements. Methods Following Levac’s 6 step scoping review guide, we searched PubMed, EMBASE, EBSCO, SCOPUS, and Web of Science from 1980 to August 2021, including English-language original articles describing assessment after undergraduate medical placements in anaesthesia and intensive care medicine. Results were reported in accordance with PRISMA scoping review guidelines. Results Nineteen articles published between 1983 and 2021 were selected for detailed review, with a mean of 119 participants and a median placement duration of 4 weeks. The most common assessment tools used were multiple-choice questions (7 studies), written assessment (6 studies) and simulation (6 studies). Seven studies used more than one assessment tool. All pre-/post-test studies showed an improvement in learning outcomes following clinical placements. No studies used objective workplace-based assessments or entrustable professional activities. One study included an account of theoretical considerations in study design. Discussion A diverse range of evidence-based assessment tools have been used in undergraduate medical assessment after anaesthesia and intensive care placements. There is little evidence that recent developments in workplace assessment, entrustable activities and programmatic assessment have translated to undergraduate anaesthesia or intensive care practice. This represents an area for further research as well as for curricular and assessment developments.